Answer:
A, B, A
Explanation:
(3)
Given
- 2x² + 10x + 12 ← factor out - 2 from each term
= - 2(x² - 5x - 6) ← factor the quadratic
Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (- 5)
The factors are - 6 and + 1, since
- 6 × 1 = - 6 and - 6 + 1 = - 5, thus
x² - 5x - 6 = (x - 6)(x + 1) and
- 2x² + 10x + 12 = - 2(x - 6)(x + 1) → A
(4)
- 81 ← is a difference of squares and factors in general as
a² - b² = (a - b)(a + b), thus
- 81
= (x² )² - 9²
=(x² - 9)(x² + 9) ← note that x² - 9 is also a difference of squares
= (x - 3)(x + 3)(x² + 9) ← in factored form
x² - 3 is not a factor → B
(5)
Given
5
- 320 ← factor out 5 from each term
= 5(
- 64) ← difference of squares
= 5(x² - 8)(x² + 8) → A